Production of coloured callus in Orthosiphon stamineus Benth and antioxidant properties of the extracted pigments - Yaacob, Jamilah Syafawati; Othman, Rashidi; Ali, Hanisah; Karsani, Saiful Anuar (Emerald Group Publishing Ltd., 2018)
Purpose The purpose of the present study is to understand the role of auxin and cytokinin in stimulating the production of pigmented callus in Orthosiphon stamineus and to gain correlation between the callus colours with their antioxidant capacity and bioactive constituents.